Stages and main tasks of the century-long control theory and system identification development. Part VIII. Datadriven terminal predictive control - Gubarev, V.; Romanenko, V. (Проблеми керування та інформатики, 2024)
This article describes some of the developed methods for finding optimal predictive control based on trajectory data, provided that they are permanently exciting. The main attention is paid to the problems of terminal control, which seems to be promising in solving many applied problems. У цій статті дається опис деяких із розроблених методів знаходження оптимального прогнозного керування траєкторними даними за умови, що вони є постійно збуджувальними. Основну увагу приділено задачам термінального керування, що, здається, є перспективним при розв’язуванні багатьох прикладних задач.